Economic barriers restraining the production of therapeutic recombinant human trypsin. Use of innovative technologies to overcome them - S. V. Ponomarenko (Фармакоэкономика, 2018)
The aim of this review is to analyze reasons for the high cost of recombinant human trypsin, technological and economic obstacles limiting trypsin production and implementation, as well as practical means to solve these problems.Materials and methods. The properties of human trypsin, the recombinant technology for its production, the marketing aspects and the prospective of enzyme therapy are addressed in this review that contains 44 references in Russian and english. Particular attention is paid to the methods that can boost the production of recombinant trypsin.Results. Trypsin purified from the mammalian pancreas has been used for over 80 years in the enzyme therapy in various diseases. Genetically engineered human trypsin is proposed to be an innovative, safe and effective therapeutic protease. However the medical use of recombinant trypsin is slowed by its very high price and insufficient production. There is a need for novel biopharmaceutical technologies, as well optimized up-stream and down-stream processes to increase the yield of active recombinant trypsin and significantly reduce the production costs. Recombinant human trypsin that is priced similar to its animal analogues is preferable in all types of enzyme therapy.Conclusion. Innovative biopharmaceutical technologies are expected to significantly reduce the production costs of recombinant human trypsin and stimulate its wider use in enzyme therapy and also in production of other therapeutic proteins.